A double blind community-based randomized trial of amoxicillin versus placebo for fast breathing pneumonia in children aged 2-59 months in Karachi, Pakistan (RETAPP). Issue 1 (December 2015) - Jehan, Fyezah; Nisar, Muhammad; Kerai, Salima; Brown, Nick; Balouch, Benazir; Hyder, Zulfiqar; Ambler, Gwen; Ginsburg, Amy; Zaidi, Anita
Abstract Background Fast breathing pneumonia is characterized by tachypnoea in the absence of danger signs and is mostly viral in etiology. Current guidelines recommend antibiotic therapy for all children with fast breathing pneumonia in resource limited settings, presuming that most pneumonia is bacterial. High quality clinical trial evidence to challenge or support the continued use of antibiotics, as recommended by the World Health Organization is lacking. Methods/design This is a randomized double blinded placebo-controlled non-inferiority trial using parallel assignment with 1:1 allocation ratio, to be conducted in low income squatter settlements of urban Karachi, Pakistan. Children 2–59 months old with fast breathing, without any WHO-defined danger signs and seeking care at the primary health care center are randomized to receive either three days of placebo or amoxicillin. From prior studies, a sample size of 2430 children is required over a period of 28 months. Primary outcome is the difference in cumulative treatment failure between the two groups, defined as a new clinical sign based on preset definitions indicating illness progression or mortality and confirmed by two independent primary health care physicians on day 0, 1, 2 or 3 of therapy. Secondary outcomes include relapse measured between days 5–14. Modified per protocol analysis comparing hazards of treatment failure with 95 % confidence intervals in the placebo arm with hazards in the amoxicillin arm will be done. Discussion This study will provide evidence to support or refute the use of antibiotics for fast breathing pneumonia paving a way for guideline change. Trial registration Clinical Trials (NIH) RegisterNCT02372461